Developing Academic Advisors and Competence Committees members: A community approach to developing CBME faculty leaders - Eleftherios Soleas (Canadian Medical Education Journal, 2020)
Introduction: Implementing competency-based medical education (CBME) at the institutional level poses many challenges including having to rapidly enable faculty to be facilitators and champions of a new curriculum which utilizes feedback, coaching, and models of programmatic assessment. This study presents the necessary competencies required for Academic Advisors (AA) and Competence Committee (CC) members, as identified in the literature and as perceived by faculty members at Queen’s University.